Shale gas in South America. From the United States’ Energy Security to the promises of a regional boom l Shale Gas en América del Sur. De La Seguridad Energética Norteamericana a Las Promesas de Un Boom Regional - Rabbia, Noemí Soledad (Revista Neiba, Cadernos Argentina Brasil, 2020)
Even though oil continues leading energy discussions worldwide the share of natural gas in total energy is expected to equal that of oil by 2030. The United States (US) has played a key role in that transition: in the last two decades a qualitative technological leap forward has driven this country to an energy revival through the exploration and production of unconventional gas and oil. Since its independence Latin America has been considered theUnited States‘ backyard with notorious emphasis in Central American andCaribbeancountries. However, the increasing energy potential that others Latin American countries like Argentina and Brazil have turned to posses in the unconventional hydrocarbons industry have led to a renewed interest in the region beyond its traditional partners. The aim of this paper is to explore what could be the interest for theUSin shale developments inSouth America; which are the countries with more potential in developing shale gas industries based on their reserves and above ground factors; and which is the current state of the foreseen South American shale revolution. Keywords: Shale gas; energy; South America; energy security. RESUMEN Pese a que el petróleo continúa liderando los debates energéticos en todo el mundo, se espera que para el 2030 la participación del gas en el total energético mundial lo iguale. Estados Unidos ha jugado un rol fundamental en dicha transición: en las últimas dos décadas un salto tecnológico cualitativo ha llevado al país a un resurgimiento energético a través de la exploración y producción de gas y petróleo no convencional. Desde su independencia, América Latina ha sido considerada el “patio trasero de Estados Unidos”, con especial énfasis en los países centroamericanos y caribeños. No obstante, el creciente potencial energético que otros países de la región como Argentina y Brasil han resultado tener en relación a la industria de hidrocarburos no convencionales ha conllevado un renovado interés norteamericano más allá de sus socios tradicionales en la región. El objetivo del presente trabajo es explorar cuál sería el interés de Estados Unidos en el desarrollo de la industria del shale en Sudamérica; cuáles son los países de esta subregión con mayor potencial para el desarrollo de shale gas en base a sus reservas y factores por encima del suelo (above ground factors); y cuál es el estado actual de la anunciada “revolución del shale en Sudamérica”. Palabras Claves: Shale gas; energía; América del Sur; seguridad energética. Recebido em: 28 ago. 2019 | Aceito em: 20 mar. 2020.